2018
DOI: 10.1371/journal.pone.0202934
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived cells improve left ventricular diastolic function and increase microvascular perfusion in advanced age

Abstract: An early manifestation of coronary artery disease in advanced age is the development of microvascular dysfunction leading to deficits in diastolic function. Our lab has previously shown that epicardial treatment with adipose-derived stromal vascular fraction (SVF) preserves microvascular function following coronary ischemia in a young rodent model. Follow-up studies showed intravenous (i.v.) delivery of SVF allows the cells to migrate to the walls of small vessels and reset vasomotor tone. Therefore we tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…We hypothesize this may be a consequence of decreased Th1 influx into the heart, as IFN-γ producing cells have been shown to support fibrosis development by direct contact with cardiac fibroblasts [75]. Finally, intravenous (IV) infusion of stromal vascular fraction (SVF) was also shown to reduce diastolic dysfunction and LV collagen content at 4 weeks after treatment in an aging rat model [98]. Similar to data regarding T-cell antagonism, reports regarding the effects of MSCs on LVH are conflicting, spanning from minimal [98] to no effect [97].…”
Section: Evidence Of Cell Therapy In Hfpef Animal Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…We hypothesize this may be a consequence of decreased Th1 influx into the heart, as IFN-γ producing cells have been shown to support fibrosis development by direct contact with cardiac fibroblasts [75]. Finally, intravenous (IV) infusion of stromal vascular fraction (SVF) was also shown to reduce diastolic dysfunction and LV collagen content at 4 weeks after treatment in an aging rat model [98]. Similar to data regarding T-cell antagonism, reports regarding the effects of MSCs on LVH are conflicting, spanning from minimal [98] to no effect [97].…”
Section: Evidence Of Cell Therapy In Hfpef Animal Modelsmentioning
confidence: 98%
“…Finally, intravenous (IV) infusion of stromal vascular fraction (SVF) was also shown to reduce diastolic dysfunction and LV collagen content at 4 weeks after treatment in an aging rat model [98]. Similar to data regarding T-cell antagonism, reports regarding the effects of MSCs on LVH are conflicting, spanning from minimal [98] to no effect [97].…”
Section: Evidence Of Cell Therapy In Hfpef Animal Modelsmentioning
confidence: 99%
“…CD11b + CD301 À Ly6C Hi Ly6G À and Ly6C Low Ly6G + cells are in AT from metabolically healthy mice Previous work in our laboratory has examined the therapeutic value of the AT SVF in improving vascular function. [16][17][18] In one study the SVF isolate lost many of its beneficial effects when the CD11b + cells were depleted. 17 Further characterization of these therapeutically relevant CD11b + cells found that approximately 45% of were also Gr1 + .…”
Section: Resultsmentioning
confidence: 99%
“…CFR is calculated as the ratio of the peak flow velocity during stress (Dobutamine) to the resting flow velocity (measured prior to Dobutamine infusion) 8 . CFR was 2.1 ± 0.35 in young rats before the IR surgery ( Figure 3B) but significantly reduced (1.1 ± 0.25) after 72 h of the IR surgery, even though the resting LAD coronary artery velocity was higher in these rats compared to data obtained before IR surgery ( Figure 3C).…”
Section: Representative Resultsmentioning
confidence: 99%
“…Transthoracic Doppler echocardiography is a noninvasive tool which allows us to study coronary artery flow velocity and CFR 5 . CFR represents the ratio of maximal coronary blood flow to the resting coronary blood flow 8 . During the stress challenge, a normal heart increases coronary blood flow up to four times above the resting value.…”
Section: Introductionmentioning
confidence: 99%